Application of Trichoderma Isolate consortium in organic fertilizer for controlling shallot twisted disease - Supriati, Lilies; Zubaidah, Siti; Djaya, Adrianson Agus; Oemar, Oesin; Ramadhan, M. M. (Universitas Lampung, 2024)
The aim of the research was to determine the effect of applying a consortium of Trichoderma spp. isolates to a type of organic fertilizer that is effective in controlling twisted disease and on the growth and yield of shallot plants. The study utilized a completely randomized design (CRD) consisting of eight treatments with four replications. The treatments examined werea= as follows: P0 = control, P1 = 5 tons per ha of chicken manure fertilizer, P2 = 5 tons per ha of chicken manure fertilizer and consortium of two Trichoderma spp. isolates, P3 = 5 tons per ha of chicken manure fertilizer and consortium of three Trichoderma spp. isolates, P4 = 5 tons per ha of chicken manure fertilizer, 20 tons per ha trichocompost, and a consortium of two Trichoderma spp. isolates, P5 = 5 tons per ha of chicken manure fertilizer, 20 tons per ha trichocompost, and consortium of three Trichoderma spp. isolates, P6 = 20 tons per ha of trichocompost and a consortium of two Trichoderma spp. isolates, and P7 = 20 tons per ha of trichocompost and a consortium of three Trichoderma spp. isolates. The results showed that the twisted disease incidence in treatment P4 was the lowest (14.52%) at 8 weeks after planting. The plant height was of 39.10 cm, with 29.8 leaves per clump at 7 WAP, and the dried bulb weight was 112.4 g per clump. In conclusion, the application of chicken manure fertilizer at a dose of 5 ton per ha, combined with 20 tons per ha of trichocompost and a consortium of two Trichoderma spp. isolates, could control twisted disease in shallot.